Answer:
[tex]f(\pi/6)=\sqrt{3}-\frac{\sqrt{3}}{2}[/tex]
Step-by-step explanation:
Given [tex]f(\theta )=3tan(\theta)-sin(2\theta )[/tex]
As we know that [tex]tan(\theta )=\frac{sin(\theta )}{cos(\theta )}[/tex]
thus we can write
[tex]f(\theta )=3\times \frac{sin(\theta )}{cos(\theta )}-sin(2\theta )\\\\\therefore f(\pi /6 )=3\times \frac{sin(\pi /6)}{cos(\pi /6)}-sin(2\cdot \pi/6)\\\\f(\pi /6)=3\times \frac{1/2}{\sqrt{3}/2}-\frac{\sqrt{3}}{2}[/tex]\
Thus
[tex]f(\pi/6)=\frac{3}{\sqrt{3}}-\frac{\sqrt{3}}{2}\\\\f(\pi/6)=\sqrt{3}-\frac{\sqrt{3}}{2}[/tex]